2008
DOI: 10.1074/jbc.m801045200
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Inhibin A Biological Activity by Alterations in the Binding Site for Betaglycan

Abstract: Inhibins A and B negatively regulate the production and secretion of follicle-stimulating hormone from the anterior pituitary, control ovarian follicle development and steroidogenesis, and act as tumor suppressors in the gonads. Inhibins regulate these reproductive events by forming high affinity complexes with betaglycan and activin or bone morphogenetic protein type II receptors. In this study, the binding site of inhibin A for betaglycan was characterized using inhibin A mutant proteins. An epitope for high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…Nevertheless, our work confirms the findings of several recent papers, which reported that a synthesized peptide representing the inhibin ␣-subunit N-terminal region has biological function in the ovary (33,34). We and others (14,20,52) have previously demonstrated that the antagonistic function of inhibin can be decreased with an antibody directed against the ␣-subunit N-terminal extension region or by deletion of the N-terminal region. Taken together, we propose a model in which the inhibin heterodimer achieves potent antagonism of activin signaling in the pituitary gonadotrope through the interaction of its ␤-subunit with ActRII/IIB enhanced by the co-receptor betaglycan, as well as through the interaction of the ␣-subunit N-terminal extension region with ALK4 (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, our work confirms the findings of several recent papers, which reported that a synthesized peptide representing the inhibin ␣-subunit N-terminal region has biological function in the ovary (33,34). We and others (14,20,52) have previously demonstrated that the antagonistic function of inhibin can be decreased with an antibody directed against the ␣-subunit N-terminal extension region or by deletion of the N-terminal region. Taken together, we propose a model in which the inhibin heterodimer achieves potent antagonism of activin signaling in the pituitary gonadotrope through the interaction of its ␤-subunit with ActRII/IIB enhanced by the co-receptor betaglycan, as well as through the interaction of the ␣-subunit N-terminal extension region with ALK4 (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Additional inhibin-binding proteins that increase the affinity of inhibin for the type II receptors are thought to be involved in mediating the antagonistic actions of inhibin. Although several candidate inhibin-binding proteins have been identified to date, only the type III TGF␤ receptor (commonly known as betaglycan) has been shown to increase the binding affinity of inhibin to the type II activin and BMP receptors (6,13,14) (Fig. 1A).…”
mentioning
confidence: 99%
“…We confirmed that betaglycan immunoreactivity was present in both the TC and GC layers of bovine antral follicles and in cultured bovine TC. Since betaglycan is considered an essential co-receptor required to facilitate the presentation of inhibin to type II signalling receptors and hence disrupt activin signalling (Lewis et al 2000, Chapman et al 2002, Makanji et al 2008, this observation prompted us to use our bovine TC culture model to evaluate the possibility that GC-derived inhibin functions as a physiological antagonist of BMP signalling in the ovary, in a manner comparable to its welldocumented role as an activin antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…A, a homology model of the mature inhibin A dimer was generated in a previous study (38). The inhibin ␣-subunit is colored orange, whereas the inhibin ␤ A -subunit is green.…”
Section: Figure 8 Homology Model Of Inhibin Amentioning
confidence: 99%
“…To identify the binding epitope on inhibin A for the ␣-subunit prodomain, residues through the finger regions of the ␣-subunit were substituted for alanine. In all, a set of 28 variants was generated (38 in the finger region of the ␣-subunit are necessary for inhibin A production and secretion (Fig. 5B, lanes 2, 4, 6, 7, and 9).…”
Section: Conservation Of the Hydrophobic Motif In The Prodomains Of Tmentioning
confidence: 99%